The Effect of the Corona Pandemic (covid-19) on the Quality of the Auditor’s Reporting by Application to Iraqi Economic Units - Ghazi Zghair, Nawfal; H. Yahya Al-Temimi, Abbas (Journal of Economics and Administrative Sciences, 2022)
Abstract:     The research aims to shed light on the Corona pandemic and its repercussions on the global economy in general, and on the activities of Iraqi economic units in particular. It also aims to show the impact of the auditor’s reporting on the effects of the Corona pandemic on economic units and its reflection on the quality of his reporting. To achieve the objectives of the research, the researcher prepared a questionnaire according to the five-point Likert scale and took into account in its preparation compatibility with the characteristics of the study community, and that the target community for this questionnaire are the economic units listed in the Iraq Stock Exchange that have completed their final accounts for the year 2020 (the year of the pandemic) , the number of (62) economic units, auditors working in the Federal Office of Financial Supervision and private auditing companies and offices, as well as academics specialized in this field, based on the following hypotheses:1- There is no statistically significant correlation between the auditor’s reporting on the impact of the Corona pandemic and the auditor’s reporting quality.2- There is no statistically significant effect between the auditor’s reporting on the impact of the Corona pandemic and the auditor’s reporting quality.     The research sample was represented by a group of auditors working in the Federal Office of Financial Supervision and private auditing companies and offices, as well as academics specialized in this field working in the accounting departments of Iraqi universities.            The most prominent finding of the research is that it is necessary for the auditor to reconsider amending the method of obtaining audit evidence, for the purpose of allowing him to finally reach a neutral technical opinion about the fairness of the financial statements, as well as relying on information technologies and other new methods in his work. In addition, the auditor should consider using new procedures to facilitate the audit process, in order to avoid delays in obtaining the information and data necessary to complete the audit in a timely manner.